A Genomic View of Escherichia Coli Diversity from Dairy Calves - Fossen, Jenna L. (My University, 2019)
Escherichia coli is a model organism for the scientific community but there are still numerous gaps in our knowledge, including its diversity within the gastrointestinal tract of dairy calves and those that survive within the farm microbiome. From this particular animal reservoir, E. coli can be transmitted into the food supply chain leading to human disease if pathogenic strains are ingested. The aim of this study was to determine if pathogenic strains of E. coli are common in calf fecal samples and if the calf’s diet and age plays a role in type and numbers of strains that are carried. Sixty-six isolates were recovered from five dairy calves ranging from 5 hours to 3 months old. Isolates were confirmed to be E. coli through protein fingerprinting profiles. The highquality bacterial genomes (n=38) were further examined for virulence factors and were classified into serogroups. These isolates displayed an average of seven different virulence factors per isolate genome. Select housekeeping genes were examined to determine isolate relatedness and genetic diversity. Seven to nine main clusters of serotypes displayed together repeatedly. The occurrence of different E. coli populations corresponded to the 12 serogroup types observed. Nine isolates from one pre-weaned calf all serotyped as O145:H28, a putative human pathogen, and their genomic variation illustrated that these are most likely clonal. The occurrence of a pathogenic serotype is particularly significant, pointing to a potential super shedder that could contaminate an entire herd. While a majority of the isolates are predicted to be non-pathogenic, this highlights the diversity among E. coli strains even when calves are reared in the same environment.
Keywords: Escherichia coli; E. coli; Dairy Calves; Genes